Blood pressure control in Australian general practice: analysis using general practice records of 1.2 million patients from the MedicineInsight database. Issue 6 (June 2021) - Roseleur, Jacqueline; Gonzalez-Chica, David A.; Bernardo, Carla O.; Geisler, Benjamin P.; Karnon, Jonathan; Stocks, Nigel P.
Abstract : Introduction: Hypertension is mostly managed in primary care. This study investigated the prevalence of diagnosed hypertension in Australian general practice and whether hypertension control is influenced by sociodemographic characteristics, duration since diagnosis or prescription of antihypertensive medications. Methods: Cross-sectional study using a large national database of electronic medical records of patients attending general practice in 2017 (MedicineInsight). Results: Of 1.2 million 'regular' patients (one or more consultations per year in every year from 2015 to 2017), 39.8% had a diagnosis of hypertension (95% confidence interval 38.7–40.9). Of these, 85.3% had their blood pressure (BP) recorded in 2017, and 54.9% (95% confidence interval 54.2–55.5) had controlled hypertension (<140/90 mmHg). BP control was lower in females (54.1%) compared with males (55.7%) and in the oldest age group (52.0%), with no differences by socioeconomic status. Hypertension control was lower among 'regular' patients recently diagnosed (6–12 months = 48.6% controlled) relative to those more than 12 months since diagnosis (1–2 years = 53.6%; 3–5 years 55.5%; >5 years = 55.0%). Among recently diagnosed 'regular' patients, 59.2% had no record of being prescribed antihypertensive therapy in the last 6 months of the study, of which 44.3% had controlled hypertension. For those diagnosed more than 5 years ago, 37.4% had no record of being prescribed antihypertensive patients, and 56% had normal BP levels. Conclusion: Although the prevalence of hypertension varied by socidemographics, there were no differences in BP assessment or control by socioeconomic status. Hypertension control remains a challenge in primary care, and electronic medical records provide an opportunity to assess hypertension management. Abstract : Supplemental Digital Content is available in the text